RESPON BIOLOGIS BEBERAPA JENIS PARASITOID PADA LALAT PENGGOROK DAUN Liriomyza huidobrensis BLANCHARD - Wahyuni, Sri; Supartha, I Wayan (AGRICA, 2009)
This research conducted to know the biological responses of leaf miner parasitoid Liriomyza huidobrensis is Hemyptarsenus varicomis Girault (Eulophidae), Opius sp (Braconidae) and Gronotoma micromorpha (Eucoilidae). Three species of parasitoid chosen as the substance of research caused by biological agent superiorities. On this research, there are some observed that is long life imagoes, preoviposition, oviposition period, after oviposition, The egg-laying rate, fertilization, daily fertilization, mortality and female proportion. This research was conducted for four-month at Ecology Laboratory and Insect Systematics and at the Green House of Pest and Plant Diseases Department, Faculty of Agriculture Udayana University in Denpasar. Used substance of host kidney bean (Vigna sinensis L ) host insect ( L. Huidobrensis ) and species of the parasitoid (H.varicornis, Opius sp and G.micromorpha) The experiments using randomized complete block design was used in this research. The observed results indicated that betwen three species of parasitoid used H.varicornis has preoviposition period and time after oviposition shortest so that to reproduce generation of H.varicornis faster than G.micromopha and Opius sp. At the meantime the fertilization level, and best female proportion produced of H.varicornis. Mortality on G.micromorpha and O.liriomyzae cause of paralyzing and host- feeding by H.varicornis. Mortality on G.micromorpha and Opius sp influential to female proportion number that produced that is the mortality of female generation caused of paralyzing and host-feeding by H. varicornis, So that fertilizing level, parasitisation level and female proportion higher happen if G.micromorpha or Opius sp released after releasing H. varicornis